2021
DOI: 10.3390/ijerph18199976
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Play Streets on Social and Community Connectedness in Rural Communities

Abstract: Promoting physical activity (PA) is a long-standing public health initiative to improve overall health and wellbeing. Innovative strategies such as Play Streets, temporary activation of public spaces to provide safe places for active play, are being adopted in urban and rural communities to increase PA among children. As part of these strategies, aspects of social and community connectedness may be strengthened. This study analyzes focus groups and interviews from rural Play Street implementation team members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Play Streets are temporary activations of public areas that create dedicated, safe space for communities to be active without entry fees 68. Play Streets have been used in urban and rural communities to encourage PA among families and have been suggested to have positive social implications for the whole community 69–73. Play Streets also require some level of policy execution to promote the implementation and sustainability of these programs 74…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Play Streets are temporary activations of public areas that create dedicated, safe space for communities to be active without entry fees 68. Play Streets have been used in urban and rural communities to encourage PA among families and have been suggested to have positive social implications for the whole community 69–73. Play Streets also require some level of policy execution to promote the implementation and sustainability of these programs 74…”
Section: Discussionmentioning
confidence: 99%
“…68 Play Streets have been used in urban and rural communities to encourage PA among families and have been suggested to have positive social implications for the whole community. [69][70][71][72][73] Play Streets also require some level of policy execution to promote the implementation and sustainability of these programs. 74…”
Section: Discussionmentioning
confidence: 99%
“…provide justi cation that Play Streets also intervenes on and provides bene ts for the implementing organizations and community(50)(51)(52)(53). Last, research is needed in additional rural settings to understand if our results and conceptual framework of Play Streets sustainability are generalizable nationally and internationally.…”
mentioning
confidence: 90%
“…Inclusive play spaces need to be designed for social interaction as well as opportunities to improve physical health ( Woolley et al 2006 ; Burke 2013 ). There is power in bringing people together—research has shown that children are more likely to engage in active play in the presence of a friend ( Umstattd Meyer et al 2021 ). Urban design of public play spaces that create opportunities for collaboration and social interaction has the potential to bring people of all ages together.…”
Section: Planning For Playmentioning
confidence: 99%
“…Creating and improving public spaces can lead to an increase in active play; however, making permanent alterations to the built environment is not always feasible ( Pollack Porter et al 2019 ). Instead, some municipalities have adopted innovative strategies such as play streets, which calls for the temporary closure of streets to create safe spaces for active play ( Umstattd Meyer et al 2019 , 2021 ; Smith et al 2022 ). Play streets have been shown to increase opportunities for active play and physical activity, as well as improving community cohesion ( Esmonde et al 2022 ; Umstattd Meyer et al 2019 ).…”
Section: Planning For Playmentioning
confidence: 99%